Forms of Modernization of Islamic Education in Türkiye in the 19th Century AD - Widia Septiani (Kasyafa: Jurnal Pendidikan Agama Islam, 2024)
Discussion of the modernization of Islamic education in Türkiye is nothing new. This remarkable writing about Turkish history in every perspective, makes the specificity of this article about the history of education born in Turkey. The learning method for educational modernization carried out in Turkey shows that it has been going on for a long time because of modernization for other Muslim countries that have been paying attention to education for a long time. Based on this article, it is discussed, in order to trace the background to the emergence of educational modernization in Turkey. This is to find forms of modernization as was done during that time in the field of education. So the birth of educational modernization is the impact of this situation that occurs in the social, political and economic system in Turkey. The factors of European expansion, rigid bureaucratic systems, the progress of European countries were the culmination of social change in Turkish society, giving rise to the Modernization of Education. As a result, policies and orientations emerged that brought progress to Turkey in the timing and future of exchanges. Educational modernization is a school model established by the government and society to use the curriculum implemented in schools. The treatment is carried out by adding modern science, let religious sciences be in their position, and disappear and then reappear and ultimately integrate religious knowledge with modern science is a progressive action in advancing education. Education in the form of Turkish modernization began in the 18th century, continued in the 18th century, 19th century to 20th century; Establishment of schools, empowerment communities, curriculum development, and rationalization of liberation in Turkey.